Early plaque formation on PTFE membranes with expanded or dense surface structures applied in the oral cavity of human volunteers - Alberto Turri; Emina Čirgić; Furqan A. Shah; Maria Hoffman; Omar Omar; Christer Dahlin; Margarita Trobos (Wiley, 2021)
Abstract Objectives This clinical randomized study aimed to evaluate the early plaque formation on nonresorbable polytetrafluoroethylene (PTFE) membranes having either a dense (d‐PTFE) or an expanded (e‐PTFE) microstructure and exposed to the oral cavity. Material and Methods Twelve individuals were enrolled in this study. In a split‐mouth design, five test membranes (e‐PTFE) with a dual‐layer configuration and five control membranes (d‐PTFE) were bonded on the buccal surfaces of posterior teeth of each subject. All study subjects refrained from toothbrushing during the study period. Specimens were detached from the teeth at 4 and 24 hr and subjected to viability counting, confocal microscopy, and scanning electron microscopy. Plaque samples were harvested from neighboring teeth at baseline, 4, and 24 hr, as control. Wilcoxon signed rank test was applied. Results No bond failure of the membranes was reported. Between the early and late time points, viable bacterial counts increased on all membranes, with no difference between the test and control. The number of Staphylococcus spp. decreased on the tooth surfaces and increased on both membranes overtime, with a significant difference compared to teeth. The total biomass and average biofilm thickness of live and dead cells were significantly greater at the d‐PTFE barriers after 4 hr. Conclusion This study demonstrated that the e‐PTFE membrane was associated with a lesser degree of biofilm accumulation during the initial exposure compared to the d‐PTFE membrane. The present experimental setup provides a valuable toolbox to study the in vivo behavior of different membranes used in guided bone regeneration (GBR).